Assessment of myocardial viability with cardiac magnetic resonance imaging. - (:unkn) unknown (My University, 2008)
With the rapid evolution of cardiovascular magnetic resonance imaging (MRI) techniques, cardiovascular MRI has become an important noninvasive diagnostic tool in cardiovascular disease. Cardiac MRI can provide high quality diagnostic information about cardiac and valvular function, coronary anatomy, coronary flow reserve and myocardial perfusion, myocardial viability, contractile reserve and cardiac metabolism. Besides, MRI can also provide prognostic information for certain cardiac diseases. Assessment of the viable myocardium is one of the major issues of the invasive cardiology. Viable myocardium has the potential for contractile recovery after reperfusion. The identification of viable myocardium is useful in predicting which patients will benefit from revascularization and have improved left ventricular ejection fraction and survival. The focus of the present article is on the clinical role of cardiac MRI in the detection of viable myocardium.